Die räumliche und zeitliche Verteilung der Schwüle und ihre graphische Darstellung (mit besonderer Berücksichtigung Afrikas) - Troll, Carl (ERDKUNDE, 1969)
The introduction to this paper reports previous attempts at a biometeorological definition of the term ’sultriness’ (Leistner, King, Herrmann, Dammann) and the quantitative determination of the so-called ’sultriness limit’ (Lancaster-Castens, Ruge, Scharlau) and sultriness values. In the last 30 years regional climate-geographical investigations using the Lancaster-Castens Curve have been carried out primarily in African countries with their longer sultry spells (Marner, Semmelhack, Scharlau, Schulze) and only a first crude attempt by Scharlau gives a world wide presentation. Investigations in Central Europe (Zimmermann, Herrmann, Lehmann, Dammann) attempt primarily to determine the frequency of sultriness and their relationship to particular weather situations. A characteristic feature of tropical climates also in high altitudes is a small annual but stronger diurnal variation in temperature, but previous analyses and graphical presentations of sultriness in the tropics have only been made on the basis of mean monthly values, neglecting the night hours. In view of this, the author presents diagrams for four stations in equatorial Africa (Tiko, Dar-es-Salaam, Tabora, Tandala) which enable seasonal and diurnal changes in the values for sultriness and comfort to be read off. This follows previous work (since 1943) for air temperature in thermo-isopleth diagrams. The new diagrams are called Kaumato-isopleths. Whereas in the permanent rain-forest climate of Tiko, sultriness values show a dominantly diurnal differentiation, Dar-es-Salaam, Tabora and Tandala show, as a result of rainy and dry seasons, a dominant seasonal variation. Tiko and Dar-es-Salaam are permanently sultry, Tabora changes between months which are always sultry, months which are completely free from sultry conditions and months with a diurnal change between sultriness and comfort. Tandala, at a height of 2040 metres, is always free from sultriness.